Emergent literacy, visual literacy i czytanie dialogowe. Potencjał edukacyjny i emancypacyjny książki obrazkowej w środowisku rodzinnym i przedszkolnym - Małgorzata Cackowska (Problemy Wczesnej Edukacji)
The article concerns contemporary perspectives on early education, early, emergent and visual literacy, and concepts of the development of cognitive, linguistic, and socio-emotional competencies by using picturebooks in the dialogic reading method. Picturebooks for small children, especially earlyconcept picturebooks, which present nouns, verbs, or adjectives and are aesthetically designed, have a great potential, and are important for the gaining of cognitive, emotional, and visual codes and ideas by the child, especially when they are introduced by an adult (parent at home or teacher in a preschool institution) through an active, dialogic manner of reading. Dialogic reading is shown and described by G.J. Whitehurst and other researchers as an interactive and stimulating method of cognitive and socio-emotional development, which enhances the children’s speaking and reading competencies independently of their class, race, or gender – which is of emancipatory significance. The main aim of the text is to turn the reader’s attention to the significance of interactive reading of precisely selected, high-quality picturebooks by parents and early education teachers in the context of children’s development.